Isobaric Vapor-Liquid Equilibria for Binary System of Ethanol (1) + Eugenol (2) at 400 and 760 mmHg - Irwan Hidayatullah; Annas Wiguno; Kuswandi Kuswandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Eugenol is the main component of clove oil, while the main impuritis of it is β-caryophyllene. Eugenol with a purity higher than 98% has a higher price than low purity eugenol. Thus, further eugenol purification process is needed. Common purification processes are extraction and distillation. In the design and simulation of the distillation process it requires a knowledge of Vapor-Liquid Equilibrium (VLE) data from a mixture of components to be separated (eugenol and ethanol) as the result of extraction process. In this work, the experimental VLE data were measured for binary mixtures of ethanol(1) + eugenol(2) at 400 and 760 mmHg. The apparatus used for this experiment is an othmer still equipped with a vacuum pump and a manometer. The experiments were performed to obtain equilibrium data (T), component concentrations in liquid phase (x), and in vapor phase (y). The binary VLE data were correlated with the Wilson, NRTL and UNIQUAC models to obtain the binary parameters. The reliability of these models were tested by comparing with experimental results using Root Mean Square Deviation (RMSD). For the system and the operation condition studied, the Wilson, NRTL and UNIQUAC models suited well and give satisfactory results based on the RMSD values.